(untitled) (Scientific journal of the Fergana State University, 2024)
Studies of flavonoids (stem, leaf, root) of the roots and surface of Physalis angulata, growing in the Tashkent region. Identification of flavonoids was carried out by comparing the retention time and quantitative content of standard samples of quercetin, 7-o-β-glugipolatein, rutin, apigenin, luteolin, hypolaetin, and gallic acid. It has been established that two flavonoids (7-o-β-glugipolatein, rutin) were first discovered in plants of the genus Physalis growing in Uzbekistan.